Early Proterozoic granite of the Taplejung Window, far eastern Lesser Nepal Himalaya - Upreti, B. N.; Rai, S. M.; Sakai, H.; Koirala, D. R.; Takigam, Y. (Journal of Nepal Geological Society, 2003)
The Lesser Himalayan Sequence of the Taplejung Window in the far eastern Nepal Himalaya can be divided into Taplejung Formation, Mitlung Augen Gneiss and Linkhim Schist (from bottom to top respectively). The window is a large domal shaped anticline plunging to the east. Two-mica granite bodies (Amarpur Granite, Kabeli Khola Granite and Tamor River Granite) have intruded the metasediments of Taplejung Formation. The granite bodies are discordant to subconcordant in relation to the country rocks. Quartz, alkali feldspar, plagioclase, muscovite, biotite and tourmaline are the main constituent minerals of the granite. Generally, the core of granite bodies is undeformed, whereas the marginal part is gneissfied with S-C mylonitic texture showing the top to south sense of shear. This sense of shear is related to the movement along the Main Central Thrust (MCT). All the samples from the granitic bodies fall under the granite field in the normative quartz-alkali feldspar-plagioclase (QAP) triangular diagram. The mineral composition shows that the granite is peraluminous in nature. The Kabeli Khola Granite has yielded a 40Ar/ 39Ar muscovite age older than 1.6 Ga indicating its magmatic age. The granites of the study area can also be correlated with the 1.8 Ga Ulleri type augen gneiss of central Nepal.